Teachers' learning through an online lesson study: an analysis from the expansive learning perspective. Issue 2 (1st February 2021) - Huang, Xingfeng; Lai, Mun Yee; Huang, Rongjin
Abstract : Purpose: This study aimed to explore how a group of Chinese primary mathematics teachers learned through conducting an online cross-cultural lesson study between China and Australia. Design/methodology/approach: An expansive learning theory was adopted to examine teachers' learning through collective activities across different activity systems. Multiple data sets including videos of research lessons, debriefings and audios of interviews were collected. From the expansive learning perspective, based on a fine-grained qualitative data analysis, various contradictions (as driving forces of learning) were identified and the ways of resolving the contradictions (as enactment of learning) were located to feature teacher learning throughout the online lesson study process. Findings: Teachers' expansive learning includes enhancing teachers' MKT and Mathematics TPACK, developing instructional design skills and capabilities in addressing challenges occurring in the virtual environment were identified. Research limitations/implications: Theoretically, the study illustrated how expansive learning theory could be utilized to examine teacher collaborative learning in the online cross-cultural lesson study. Practically, this study showed that reiterative cycles and experts' facilitation are crucial to expansive learning for linking research to classroom practice. However, this study did not focus on student learning in the virtual environment. Australian teachers' reciprocal learning through the online lesson study also requires further exploration. Originality/value: Both online lesson study and cross-cultural collaboration are innovative. The expansive learning lens are creatively used to examine the complexity of teacher learning in such a novel environment.